2017
DOI: 10.1007/s12640-017-9721-1
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioural Toxicity of Iron Oxide Nanoparticles in Mice

Abstract: Iron oxide nanoparticles (FeO-NPs) are widely used in various biomedical applications, extremely in neurotheranostics. Simultaneously, FeO-NP usage is of alarming concern, as its exposure to living systems causes deleterious effects due to its redox potential. However, study on the neurobehavioural impacts of FeO-NPs is very limited. In this regard, adult male mice were intraperitoneally administered with FeO-NPs (25 and 50 mg/kg body weight) once a week for 4 weeks. A significant change in locomotor behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 74 publications
5
28
0
Order By: Relevance
“…On the other hand, it has been shown that high levels of ROS can cause damage to macromolecules . The results of our study are in agreement with previous studies …”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…On the other hand, it has been shown that high levels of ROS can cause damage to macromolecules . The results of our study are in agreement with previous studies …”
Section: Discussionsupporting
confidence: 94%
“…Malondialdehyde is one of the important indicators for evaluating LPO . The results of our study in this regard are also in agreement with previous studies . Fe 2 O 3 NPs cause OS by disturbing the status of oxidants and antioxidants .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations